Apical pruning on cucumber seed yield and quality - Nakada, P. G. [UNESP]; Claudio, M. T.R. [UNESP]; Tavares, A. E.B. [UNESP]; Bardiviesso, E. M.; Cardoso, A. I.I. [UNESP] (International Society for Horticultural Science (ISHS), 2019)
Apical pruning is a process used in many species of the Cucurbiceae family and its goal is to increase fruit yield. This study evaluates the effect of pruning the main stem on cucumber seed yield and quality. This experiment was undertaken in Sao Manuel, State of Sao Paulo, between July and December 2011. A line of Brazilian cucumber (PEP 788), from Unesp/FCA Germplasm Bank was used in this experiment. Four different treatments were performed: no pruning; pruning of the apical meristem on the sixth, eighth and tenth node. The characteristics under evaluation were: number of fruits plant-1, seed yield, number of branches, length, diameter, fruit weight and a physiological quality analysis (germination, first germination count, weight of a thousand seeds, transplant emergence and emergence speed index). The experimental design was randomized blocks with six repetitions and six plants per plot. Tukey’s test at 5% significance was applied to compare means. Pruning did not increase fruit number and seed yield. It also did not affect physiological quality. Plants pruned on the eighth and tenth node produced a higher number of lateral branches.
Keywords: Branching; Cucumis sativus; Fructification; Germination; Vigor